2003
DOI: 10.1385/endo:22:2:151
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Improves Insulin Resistance in Nondiabetic Dyslpidemic Patients

Abstract: Statins have multiple actions, independent of their classical effects on lipoproteins. The data about the effects of statins on insulin resistance is controversial. This study was designed to search the statin effects on nondiabetic dyslipidemic patients. Thirty-five (17 male, 18 female) consecutive dyslipidemic patients 54.25 +/- 8.81 yr were enrolled in the study. After a standard follow-up period of lifestyle modification, the patients were given fluvastatin 40 mg/d for 8 wk. Serum analyses were done both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
3
31
2
1
Order By: Relevance
“…That factor, together with the short 3-month study period of Sari et al, might explain why that study detected no improvement in HOMA-IR. As in our study, Sonmez et al 33 reported an improvement in insulin resistance in 35 hypercholesterolaemic patients treated with fluvastatin. We also found that there was no correlation between changes in patient lipid profile and the observed improvement in insulin resistance, suggesting potential fluvastatin pleiotropism.…”
Section: Discussionsupporting
confidence: 81%
“…That factor, together with the short 3-month study period of Sari et al, might explain why that study detected no improvement in HOMA-IR. As in our study, Sonmez et al 33 reported an improvement in insulin resistance in 35 hypercholesterolaemic patients treated with fluvastatin. We also found that there was no correlation between changes in patient lipid profile and the observed improvement in insulin resistance, suggesting potential fluvastatin pleiotropism.…”
Section: Discussionsupporting
confidence: 81%
“…Recent clinical trials demonstrated that PPAR-␣ or PPAR-␥ agonist improved the outcome of atherosclerotic heart disease (10,14), whereas dual-PPAR agonist did not (34). In addition, statins improved insulin resistance (41) and antioxidant activities, including the restoration of Cu/ZnSOD activity (48), prevented the development of diabetes, reduced lipid levels (13,38), and improved clinical outcome in patients with hypercholesterolemia (1). These results, taken together with those of the present study, indicate that pitavastatin may selectively activate PPAR-␥ and Cu/ ZnSOD in hypercholesterolemia as pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…These "pleiotropic effects" of statins include improvement of endothelial function, antithrombotic actions, plaque stabilization, reduction of the vascular inflammatory process, and an antioxidant function through the inhibition of NAD(P)H oxidase or the increase in SOD activity (3,6,26,32). Statins are also reported to improve insulin resistance (41) and antioxidant properties, including the restoration of Cu/ZnSOD activity (48), and prevent the development of diabetes in patients with hypercholesterolemia (13,38). Taken together, these observations allow one to assume that statins may have antiatherogenic actions through PPAR and Cu/ZnSOD activation, in addition to antidyslipidemic actions.…”
mentioning
confidence: 99%
“…In addition, statins have several pleiotropic effects unrelated to lipid levels including reduced inflammation, improved endothelial function (14) and improved insulin sensitivity (15). Statins may improve insulin resistance even in nondiabetic patients (16), and may actually have a protective effect against the development of diabetes in the general population (17). We therefore hypothesized that statins would demonstrate a protective effect against new-onset diabetes in renal transplant recipients (RTR), whose risk factors for diabetes are well defined (2,10) and somewhat different (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%